The 1727 Statutes of Herrnhut - Peucker, Paul (Journal of Moravian history, 2020)
In 1727 Zinzendorf issued two regulatory documents for the community of Herrnhut, the Manorial Commandments and the Brotherly Agreement, that regulated civic affairs and spiritual matters for the new town and defined the settlement as a Philadelphian community. Here an English translation of these two documents, together with the German original, is presented. The edition and translation are based on the original manuscript versions of both the Manorial Commandments and the Brotherly Agreement as found in the Unity Archives in Herrnhut, Germany.